Expectations and Decisions in the Volunteer’s Dilemma: Effects of Social Distance and Social Projection - Krueger, Joachim I.; Ullrich, Johannes; Chen, Leonard J. (Frontiers in Psychology, 2016)
In a Volunteer’s Dilemma (VoD) one individual needs to bear a cost so that a public good can be provided. Expectations regarding what others will do play a critical role because they would ideally be negatively correlated with own decisions; yet, a social-projection heuristic generates positive correlations. In a series of 2-person-dilemma studies with over 1,000 participants, we find that expectations are indeed correlated with own choice, and that people tend to volunteer more than game-theoretic benchmarks and their own expectations would allow. We also find strong evidence for a social-distance heuristic, according to which a person’s own probability to volunteer and the expectation that others will volunteer decrease as others become socially more remote. Experimentally induced expectations make opposite behavior more likely, but respondents underweight these expectations. As a result, there is a small but systematic effect of over-volunteering among psychologically close individuals.